Vitamin D Intake and Factors Associated With Self-Reported Vitamin D Deficiency Among US Adults: A 2021 Cross-Sectional Study - Andrade, Jeanette M.; Grandoff, Philip G.; Schneider, Sydney T. (Frontiers in Nutrition, 2022)
Vitamin D deficiency is a global issue that may be attributed to various factors such as dietary habits, sun exposure, age, race and chronic conditions. The purpose of this study was to determine the relationship between vitamin D intake from food/supplements and factors that may be associated with self-reported vitamin D deficiency among US adults. A cross-sectional online study was conducted among 1,637 adults using a 38-item questionnaire. Frequency counts and percentages were tabulated and a multiple linear regression was performed. Statistical significance was determined at p < 0.05. Participants (n = 554, 33.8%) were considered vitamin D deficient and consumed an average of 347.05 ± 307.8 IUs of vitamin D through foods/beverages. The multivariate linear regression showed no statistically significant difference with vitamin D intake from foods/beverages on vitamin D deficiency status. Significant positive correlations were seen with vitamin D deficiency status and certain chronic conditions such as chronic kidney disease (p = 0.04), depression (p < 0.001), diabetes (p = 0.02), and vitamin D supplement use (p < 0.001). Significant negative correlations were observed with vitamin D deficiency status and age (p = 0.01) and sun exposure (p < 0.001). Future focus should be on educating individuals about factors associated with vitamin D to reduce the prevalence of vitamin D deficiency.